Guinea - Decentralization in Guinea : Strengthening Accountability for Better Service Delivery - World Bank (Washington, DC, 2012)
The purpose of this report is to present reform options for the implementation of the new code that would strengthen accountability in service delivery. The report is structured as follows: chapter one discusses how decentralization can be an effective tool for improving service delivery and local governance. Chapter two assesses progress in fiscal, administrative and political decentralization, scrutinizes their impact on accountability relationships and makes recommendations to further decentralization, in line the new code. Chapter three analyses current arrangements for service delivery in two sectors (water and education), maps out strengths and weaknesses of existing accountability relationships and makes recommendations, drawing on existing innovative practices in Guinea and/or the region. Chapter four offers recommendations to manage change and maintain the momentum for reform. Chapter five concludes with an outlook.